Milk extraction for human consumption from N'Dama cattle under village management conditions in The Gambia - Agyemang, K.; Jeannin, P.; Grieve, A.S.; Bah, M.L.; Dwinger, R.H. (ILCA/ILRAD, 1988)
Studies milk production for human consumption from N'Dama cattle under village management conditions in The Gambia. Discusses herd management and milk recording schemes. Examines milk-fat yield, milk protein, milk offtake, calf growth, calf mortality, lactation length and yield and milking frequency.